STRATEGI PERBAIKAN BIMBINGAN M,IZHASTSWA PROGRAM PENGA1,AMAN 1,APANGAN DALAM EVALUASI PEMBELAJARAN BAHASA INDONESIA - Pujiati Suyata Pujiati Suyata (LPMPP Universitas Negeri Yogyakarta, 1999)
The objective of the research concerned here was toimprove the guidance given to student teachers evaluatingpupil's performance in classes of Bahasa Indonesia. Theproblem addressed was the appropriate strategy and techniqueto use in the improvement of the guidance, especiallyconcerning the final learning evaluation, daily testing evaluation,and quarterly evaluation.The research applied a classroom action research modelconsisting of three stages: (1) training in conducting thefinal learning evaluation, two cycles, (2) training in conductingthe daily testing evaluation, two cycles, and (3) trainingin conducting the quarterly evaluation, one cycle. Eachcycle consisted of four steps, i.e., action preparation, actionimplementation, monitoring and evaluation, and analysisand reflection. The training in evaluation was focussedon the communicative evaluation technique covering anumber of aspects: linguistic knowledge and the skills ofreading comprehension, listening comprehension, speaking,and writing. The materials of the training concernedthe match between test items and the goals of the learningevaluation, constiuction of the table of items' specifications,items' writing and reviewing, test administering, and analysisand interpretation of test results. The data were obtainedfrom an analysis on the lesson plan and aspects of test construction:construction of the table of items' specifications,items' writing and reviewing, test administering, and analysisand interpretation concerning test items. Validation ofdata was done through triangulation across methods andsources and inter-researcher discussion. The data wereanalyzed according to the action stages.